The Danube River – Link of Cooperation and Dialogue - Repez, Filofteia; Gheorghe, Stefan (Acta Universitatis Danubius. Relationes Internationales, 2024)
The Danube River has a special significance for the states and localities through which it passes. Various events, historical, political, cultural, sports, etc. have been held over time in the Danube region; The Danube united and divided at the same time, being the silent witness of numerous events. Europe, the lady of the Danube, as Nicolae Iorga calls her, is the owner of the most international hydrographic basin in the world - the Danube river basin. More than 80 million people from 19 countries live and work here. The multiple importance of this river and the need to ensure its security is emphasized often and in various ways. Starting from the presentation of some aspects that highlight the importance of the Danube for the states and the places it crosses, we will continue with detailing some examples of cooperation and dialogue actions in the Danube region that contribute to ensuring Danube security and the formation of a Danube cult, and we will finish highlighting a remarkable aspect of the Danube, that of a source of inspiration. In this way, the article aims to pay homage to this cherished river, before which many have bowed.